Approaches to Artistic Style Suppression: An Evaluation Framework for Copyright Compliance in Generative Artificial Intelligence - Cumming, Aedan (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEng)--Stellenbosch University, 2026.